Group Investigation Learning Model Assisted by Card Sort Media on Social Attitudes of Elementary School - Jayanti, Kadek Putri Rani; Wulandari, I Gusti Agung Ayu; Agetania, Ni Luh Putu (Universitas Pendidikan Ganesha, 2025)
The low level of social attitudes among elementary school students, such as a lack of empathy, cooperation, and concern for others, is reflected in behaviors such as indifference, mocking peers, and reluctance to help classmates in learning. This condition highlights the importance of implementing a learning model that can effectively cultivate social values from an early age. This study aims to examine the effect of the Cooperative Learning model of the Group Investigation type assisted by card sort media on students' social attitudes in the Pancasila Education subject in third-grade elementary school. This research is a quasi-experimental study using a non-equivalent post-test only control group design. The study population consisted of 152 third-grade elementary school students. Data were collected using a questionnaire instrument, and the data were analyzed using inferential statistics through a t-test. The hypothesis testing results showed that at a significance level of 0.5, the value of tcount = 10.433 and ttable = 1.687, indicating that tcount > ttable, which means H0 is rejected and H1 is accepted. Thus, there is a significant effect of the implementation of the Cooperative Learning model of the Group Investigation type assisted by card sort media on students' social attitudes. This study implies that the learning process can be more effective and efficient in instilling social and moral values through the Pancasila Education subject and is expected to help students develop social attitudes in line with educational goals.